Nanomaterials and Nanotechnologies for Marine and Membrane Antifouling Applications (Journal of Research Updates in Polymer Science, 2023)
The major responsibility of the marine industry includes the global transportation of goods, materials, and people. To cater the longstanding challenges like degradation of materials and biofouling, it has embraced nanotechnology solutions. Nano-technology offered numerous products such as nano-ZnO, nano alumina, and nano silica, etc. to deal with corrosion in a cost-effective manner. Similarly, to address the biofouling in the aquatic environment, hybrid nanocomposites of organic-inorganic materials, photocatalytic nanomaterials, metal and metal oxide nanomaterials (nanoparticles, nanowires, nanorods), etc. are employed as viable agents to create non-toxic or low-toxic antifouling coatings. On the other hand, membrane separation technology plays a significant role in various industries including water treatment plants, food, medicine, pharmacy, biotechnology, etc. in addition to the domestic arena for the purification of drinking water. Such a wonderful technology is being totally disturbed by a troublesome problem and a predominant barrier called membrane fouling, which drastically limits the commercialization of the membranes and the whole membrane industrial technology as well. Hence, this review exclusively throws light on the role of nanomaterials and nanotechnologies developed for the prevention of fouling that occurs on submerged structures and membranes as well and to give possible solutions with increased resilience against challenges to come.